Metaphors and something else in the symbolical network of Paradise and Cain and Abel by Ambrose of Milan (Circe de clásicos y modernos, 2018)
The paper analyzes certain symbolical projections on Paradise and Cain and Abelby Ambrose of Milan that set the reflections on a significance level that surpasses the philosophical or theological approach. So, the article studies the body metaphor in Par. I, 7-9 and the shepherd metaphor in Cain et Ab. VI, 24, where metaphorical enunciation allows the location of images on the semantic field of politic and social concerns, within common benefit idea is the most relevant.
Keywords: mataphor; exegesis; semantic field; common benefit; Ambrose of Milan